Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery
By introducing specific elements and structural characteristics into the positive active substance of lithium-ion secondary batteries, the problem of insufficient battery cycle maintenance rate is solved and higher battery performance and stability is achieved.
Patent Information
- Application Number
- JP2023171591
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-02
- Publication Date
- 2025-04-14
AI Technical Summary
There is room for improvement in the circulation and maintenance rate of existing lithium-ion secondary batteries, especially during long-term use and charging and discharging.
Using positive electrode active substances containing Li, Mn, Ni and M elements (such as Nb, Ta, Mo, W), the specific requirements include having a layered structure and specific Raman spectroscopic peak and width ratios, as well as specific compositional formulas and physical properties.
The high cycle maintenance rate of lithium-ion secondary batteries is achieved, and the performance of the battery during long-term use and charging and discharging is improved by stabilizing the structure of the positive electrode active material.
Smart Images

Figure 2025062478000002 
Figure 2025062478000003 
Figure 2025062478000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, and a lithium secondary battery. [Background technology]
[0002] The battery performance of a lithium secondary battery varies depending on the composition and crystalline state of the positive electrode active material for the lithium secondary battery.
[0003] A material represented by LiMeO2 (Me is a metal element containing Ni and Mn) with a layered structure is known as a positive electrode active material for lithium secondary batteries. Studies are being conducted to replace part of the Me in LiMeO2 with a high-valence metal element such as W.
[0004] For example, Patent Document 1 discloses a compound having the general formula Li z Ni 1-x-y Co x M y The present invention discloses a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising the steps of: mixing and immersing a lithium metal composite oxide powder having a layered crystal structure composed of primary particles represented by the formula (x, y, z) of 02 (where 0≦x≦0.35, 0≦y≦0.35, 0.95≦z≦1.30, and M is at least one element selected from Mn, V, Mg, Mo, Nb, Ti, and Al) and secondary particles formed by aggregation of the primary particles in an alkaline solution having a tungsten concentration of 0.1 to 2 mol / L in which a tungsten compound is dissolved, in such a manner that the solid-liquid ratio of the lithium metal composite oxide powder to the water content in the alkaline solution is in the range of 200 to 2500 g / L; and then subjecting the mixture to solid-liquid separation to obtain a tungsten mixture in which tungsten is uniformly dispersed on the surfaces of the primary particles of the lithium metal composite oxide; and heat-treating the tungsten mixture to form a compound containing tungsten and lithium on the surfaces of the primary particles of the lithium metal composite oxide. It is disclosed that a battery using the positive electrode active material thus obtained has a high capacity and can obtain a higher output while suppressing an increase in the amount of gas generated. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2016 / 171081A1 Summary of the Invention [Problem to be solved by the invention]
[0006] As the range of applications of lithium secondary batteries continues to expand, there is a demand for further improvements in the cycle retention rate of lithium secondary batteries. The present invention has been made in view of the above circumstances, and has an object to provide a positive electrode active material for a lithium secondary battery that can achieve a lithium secondary battery with a high cycle retention rate, as well as a positive electrode for a lithium secondary battery and a lithium secondary battery that include the positive electrode active material for a lithium secondary battery. [Means for solving the problem]
[0007] The present invention includes the following [1] to [8]. [1] A positive electrode active material for a lithium secondary battery, comprising Li, Mn, Ni, and an M element, the M element being at least one element selected from the group consisting of Nb, Ta, Mo, and W, and satisfying the following requirements (1) and (2): (1) It has a layered structure. (2) In Raman spectroscopy with an excitation wavelength of 532 nm, the peak intensity is 580-610 cm -1 The peak is P1, 630-670 cm -1 is P2, the peak intensity of P1 is I1, and the peak intensity of P2 is I2, I2 / I1 is 0.20 or more and 0.68 or less. [2] The positive electrode active material for a lithium secondary battery according to [1], wherein F2 / F1 is 0.55 or more and 1.35 or less, where F1 is the half width of P1 and F2 is the half width of P2. [3] The positive electrode active material for a lithium secondary battery according to [1] or [2], represented by the following composition formula (I): Li 1+aNi x Mn y M b M’ c O2···(I) [In the above compositional formula (I), 0 ≦ a ≦ 0.5, 0 < x < 1, 0 < y < 1, a + x + y + b + c = 1, 0 < b ≦ 0.1, and 0 ≦ c ≦ 0.3 are satisfied, and M’ is at least one element selected from the group consisting of P, B, Co, Ti, Zr, and Al.] [4] The BET specific surface area is 0.2 m 2 / g or more and 2 m 2 / g or less, and the positive electrode active material for a lithium secondary battery according to any one of [1] to [3]. [5] In the powder X-ray diffraction measurement using CuKα rays, X2 / X1, which is the ratio of the peak intensity X2 of the peak existing in the range of 2θ = 20.7 ± 1° to the peak intensity X1 of the peak existing in the range of 2θ = 18.7 ± 1°, is 0.005 or more and 0.06 or less, and the positive electrode active material for a lithium secondary battery according to any one of [1] to [4]. [6] The highest among the peak intensities obtained within the range where the I1 is 200 cm -1 or more and 1000 cm -1 or less, and the positive electrode active material for a lithium secondary battery according to any one of [1] to [5]. [7] A positive electrode for a lithium secondary battery containing the positive electrode active material for a lithium secondary battery according to any one of [1] to [6]. [8] A lithium secondary battery containing the positive electrode according to [7].
Advantages of the Invention
[0008] According to the present invention, it is possible to provide a positive electrode active material for a lithium secondary battery capable of achieving a lithium secondary battery with a high cycle retention rate, and a positive electrode for a lithium secondary battery and a lithium secondary battery containing the positive electrode active material for a lithium secondary battery.
Brief Description of the Drawings
[0009] [Figure 1] It is a schematic configuration diagram showing an example of a lithium secondary battery. [Diagram 2]FIG. 1 is a schematic diagram showing the overall configuration of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The definitions of terms used in this specification are as follows. Metal Composite Compound (MCC) is also referred to below as "Metal Composite Compound." Cathode Active Material for Lithium Secondary Batteries The Commercial Application Programmable Integrated Circuit for Lithium Secondary Batteries (CAM) will be referred to as "CAM" below. "Ni" indicates the element Ni, not the simple nickel metal. The same applies to other elements such as Co and Mn. For example, if the range is 0.2 to 2 m 2 / g" indicates 0.2m 2 / g to 2m 2 / g, with the lower limit being 0.2m 2 / g and the upper limit of 2m 2 / g means a range of numbers inclusive. A lithium secondary battery refers to a battery in which an electrolyte (such as a non-aqueous electrolyte or a solid electrolyte) is disposed between a positive electrode and a negative electrode, and charging and discharging are performed by lithium ions moving between the positive electrode and the negative electrode via the electrolyte.
[0011] The methods for measuring each parameter of CAM in this specification are as follows.
[0012] (Raman spectroscopy parameters) The Raman spectroscopic analysis parameters of CAM can be measured using a laser Raman microscope (e.g., Raman Touch, manufactured by Nanophoton Corporation). Measurement conditions include an excitation wavelength of 532 nm, a slit width of 50 μm, and a diffraction grating of 600 gr / mm. Based on the obtained Raman spectroscopic spectrum, a mixture of a Gaussian function and a Lorentz function (the least squares method) was used to determine the peak intensity at 580 to 610 cm. -1The peak is P1, 630-670 cm -1 The peak is identified as P2, and the peak intensity I1 and half width F1 of the P1, and the peak intensity I2 and half width F2 of the P2 can be determined.
[0013] (composition) The composition of each element in CAM can be measured by inductively coupled plasma emission spectrometry (ICP). For example, after dissolving CAM in hydrochloric acid, the amount of each element can be measured using an inductively coupled plasma emission spectrometer (e.g., SPS3000, manufactured by SII NanoTechnology Co., Ltd.).
[0014] (BET specific surface area) BET specific surface area of CAM (unit: m 2 The specific surface area (A / g) can be measured by the BET (Brunauer, Emmett, Teller) method. In measuring the BET specific surface area, nitrogen gas is used as the adsorption gas. For example, 1 g of CAM powder can be dried in a nitrogen atmosphere at 105°C for 30 minutes, and then measured using a BET specific surface area meter (for example, Macsorb (registered trademark) manufactured by Mountec Co., Ltd.).
[0015] (50% cumulative volumetric grain size D 50 ) The 50% cumulative volumetric grain size of CAM (unit: μm, hereafter referred to as "D 50 ") can be determined from the particle size distribution of CAM measured by a laser diffraction scattering method. Specifically, 0.1 g of CAM powder is added to 50 ml of a 0.2 mass % aqueous solution of sodium hexametaphosphate to obtain a dispersion in which the powder is dispersed. Next, the particle size distribution of the obtained dispersion is measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments) to obtain a cumulative particle size distribution curve based on volume. In the obtained cumulative particle size distribution curve, the particle size value at 50% accumulation from the fine particle side is D 50 It is.
[0016] (XRD pattern, X2 / X1 measurement) The XRD pattern of CAM can be obtained by powder X-ray diffraction measurement. Specifically, a powder X-ray diffractometer (e.g., Rigaku Corporation, UltimaIV) is used to fill a dedicated substrate with CAM powder, and a Cu-Kα source is used to perform measurement under the conditions of a diffraction angle 2θ=10° to 90°, a sampling width of 0.02°, and a scan speed of 4° / min to obtain an XRD pattern. Next, the integrated powder X-ray analysis software JADE is used to calculate the peak intensity X1 of the peak present in the range of 2θ=18.7±1° in the XRD pattern and the peak intensity X2 of the peak present in the range of 2θ=20.7±1°. At this time, the background is removed by setting the average value of the peak intensity at 10.25°±0.25° to 0. The value obtained by dividing X2 by X1 is X2 / X1.
[0017] (Cycle maintenance rate) A lithium secondary battery is produced using the CAM, and the cycle retention rate is measured.
[0018] <Preparation of positive electrodes for lithium secondary batteries> A paste-like positive electrode mixture is prepared by adding and kneading CAM, a conductive material (acetylene black), and a binder (PVdF) so that the composition is CAM:conductive material:binder = 92:5:3 (mass ratio). When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.
[0019] The obtained positive electrode mixture is applied to a 40 μm thick Al foil as a current collector and vacuum dried at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.
[0020] <Preparation of lithium secondary battery> The following operations are carried out in a glove box under an argon atmosphere. The above-mentioned positive electrode for lithium secondary battery is placed with the aluminum foil side facing down on the bottom cover of a part for coin-type battery R2032 (manufactured by Hosen Co., Ltd.), and a laminated film separator (thickness 16 μm) made of a heat-resistant porous layer laminated on a polyethylene porous film is placed on top of it. 300 μl of electrolyte is poured here. The electrolyte used is a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a ratio of 30:35:35 (volume ratio) in which LiPF6 is dissolved to make 1 mol / l. Next, metallic lithium is used as the negative electrode, placed on the top of the separator, and the top lid is placed over the gasket and crimped with a crimping machine to produce a lithium secondary battery (coin-type half cell R2032).
[0021] <Cycle test> Using the produced lithium secondary battery, a charge / discharge cycle repetition test is carried out in the following manner, and the cycle retention rate is calculated.
[0022] Repeated charge / discharge cycle testing The lithium secondary battery is left to stand at room temperature for 12 hours to allow the separator and the positive electrode mixture layer to be sufficiently impregnated with the electrolyte. Next, at a test temperature of 25°C, the charging and discharging currents are set to 0.2 CA, and constant current / constant voltage charging and constant current discharging are performed, respectively. The maximum charging voltage is 4.6V / 4.5V, and the minimum discharging voltage is 2.5V / 2.0V. Next, constant current / constant voltage charging and constant current discharging were repeated under the following conditions at a test temperature of 25° C. The charge / discharge cycle was repeated 50 times. Charging: Current setting value 1CA, maximum voltage 4.5V / 4.6V, constant current constant voltage charging Discharge: Battery setting value 1CA, minimum voltage 2.5V / 2.0V, constant current discharge The cycle retention rate is calculated from the discharge capacity at the 1st cycle and the discharge capacity at the 50th cycle using the following formula. Cycle retention rate (%) = 50th cycle discharge capacity (mAh / g) / 1st cycle discharge capacity (mAh / g) × 100
[0023] <Positive electrode active material for lithium secondary batteries> The CAM contains Li, Mn, Ni, and M elements. The M element is at least one element selected from the group consisting of Nb, Ta, Mo, and W. The CAM satisfies the following requirements (1) and (2). (1) It has a layered structure. (2) In Raman spectroscopy with an excitation wavelength of 532 nm, the peak intensity is 580-610 cm -1 The peak is P1, 630-670 cm -1 When the peak intensity of P1 is P2, the peak intensity of P1 is I1, and the peak intensity of P2 is I2, I2 / I1 is 0.20 to 0.68.
[0024] <Requirement (1)> The crystal structure of CAM is a layered structure. The crystal structure of CAM is preferably a layered rock-salt structure, and more preferably a hexagonal crystal structure or a monoclinic crystal structure.
[0025] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P 31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63 , P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.
[0026] In addition, the monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.
[0027] Among these, in order to obtain a lithium secondary battery having a high cycle retention rate, it is more preferable that the crystal structure of CAM is a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to the space group C2 / m.
[0028] (Confirmation of crystal structure) The crystal structure of CAM can be confirmed using a powder X-ray diffraction apparatus (eg, Ultimal V, manufactured by Rigaku Corporation).
[0029] <Requirement (2)> CAM contains LiMeO2 (Me is a metal element, including Ni and Mn) having a layered structure. CAM also contains M element. M element is an element with a higher valence than Mn and Ni in an oxide state. Also, the ionic radius of M element is larger than that of Mn. Therefore, it is considered that the M element replaces (dopes) a part of Me in LiMeO2, and the distance of Mn-O bonds existing around the doped Me changes. Specifically, by doping a part of Me (Mn) in LiMeO2 with M element, a part of -Mn-O-Mn- bonds becomes -MO-Mn- bonds. As described above, M element in CAM is higher valence than Mn and has a larger ionic radius, so that the distance of Mn-O bonds in -MO-Mn- bonds is considered to be shorter than the distance of Mn-O bonds in -Mn-O-Mn- bonds. Also, it is considered that the shorter distance of Mn-O bonds means that the strength of Mn-O bonds is high. The inventors of the present application have found that when CAM contains at least a specific amount of -MO-Mn- bonds, which are Mn-O bonds with high bond strength, the structure of CAM is stabilized and the cycle retention rate is improved.
[0030] P1 is considered to be a peak derived from the Mn-O bond in the -Mn-O-Mn- bond. P2 is considered to be a peak derived from the Mn-O bond in the -MO-Mn- bond. It is considered that I1 increases as the number of -Mn-O-Mn- bonds increases. It is considered that I2 increases as the number of -MO-Mn- bonds increases. In other words, I2 / I1 is considered to indicate the ratio of the number of -MO-Mn- bonds to the number of -Mn-O-Mn- bonds contained in CAM.
[0031] The inventors of the present application have found that when the ratio of the number of -MO-Mn- bonds to the number of -Mn-O-Mn- bonds, i.e., I2 / I1, is within a specific range, the structure of CAM is stabilized and the cycle retention rate is improved.
[0032] I2 / I1 is preferably 0.22 or more, more preferably 0.24 or more, and even more preferably 0.25 or more. I2 / I1 is preferably 0.60 or less, more preferably 0.50 or less, and even more preferably 0.45 or less. I2 / I1 is preferably 0.22 to 0.60, more preferably 0.24 to 0.50, and even more preferably 0.25 to 0.45. The I2 / I1 ratio being within the above range means that the ratio of the number of -MO-Mn- bonds to the number of -Mn-O-Mn- bonds is within a certain range, i.e., the Mn-O bond contains a specific amount or more of -MO-Mn- bonds with high strength, which results in a stable structure of the CAM and an improved cycle retention rate.
[0033] I1 is 200-1000cm -1 In other words, it is preferable that the intensity of the peak obtained within the range of 200 to 1000 cm is the highest. -1 In the range, the position of the peak with the highest peak intensity is 580 to 610 cm -1(P1) is preferable. When I1 is the highest, it means that the main crystal structure of CAM is a hexagonal structure belonging to the space group R-3m. Also, when I1 is the highest, it means that the Mn-O bond in the -Mn-O-Mn- bond effectively contributes to the stability of the crystal structure. Therefore, the cycle retention rate is likely to be improved.
[0034] When the half-width of P1 is F1 and the half-width of P2 is F2, F2 / F1 is preferably 0.55 or more, more preferably 0.60 or more, even more preferably 0.70 or more, and particularly preferably 0.75 or more. F2 / F1 is preferably 1.35 or less, more preferably 1.30 or less, even more preferably 1.15 or less, and particularly preferably 1.00 or less. F2 / F1 is preferably 0.55 to 1.35, more preferably 0.60 to 1.30, even more preferably 0.70 to 1.15, and particularly preferably 0.75 to 1.00. F1 is considered to indicate the distribution of the distance (strength) of Mn-O bonds in the -Mn-O-Mn- bonds contained in CAM. That is, a small F1 means that the distribution of the Mn-O bond distances in the -Mn-O-Mn- bonds contained in the CAM is small, and the Mn-O bond distances in the -Mn-O-Mn- bonds are relatively uniform. F2 indicates the distribution of the Mn-O bond distances (strengths) in the -MO-Mn- bonds contained in the CAM. That is, a small F2 means that the distribution of the Mn-O bond distances in the -MO-Mn- bonds contained in the CAM is small, and the Mn-O bond distances in the -MO-Mn- bonds are relatively uniform. When F2 / F1 is equal to or greater than the lower limit, it means that the distance of the Mn-O bond is short and the strength of the Mn-O bond is high. As a result, the structure of the CAM is stabilized and the cycle retention rate is likely to improve. When F2 / F1 is equal to or less than the upper limit, the stress generated when the CAM expands or contracts during charging and discharging can be alleviated, and the CAM is less likely to crack. As a result, the cycle retention rate is likely to improve.
[0035] F1 is 10cm-1 More than 20cm is preferable. -1 More preferably, it is 30 cm or more. -1 More preferably, F1 is 55cm or more. -1 Preferably less than 50cm -1 It is more preferable that it is less than 40 cm. -1 It is more preferable that F1 is 10 to 55 cm. -1 It is preferable that the distance is 20 to 50 cm. -1 More preferably, it is 30 to 40 cm. -1 It is even more preferable that: When F1 is equal to or greater than the lower limit, the diffusion resistance at the crystal interface is reduced, and non-uniform reactions at the interface are less likely to occur, leading to an improvement in cycle retention rate.When F1 is equal to or less than the upper limit, the crystallinity is improved, leading to an improvement in cycle retention rate.
[0036] F2 is 10cm -1 It is preferable that the length is at least 15cm. -1 More preferably, 25 cm or more. -1 More preferably, F2 is 80 cm or more. -1 Preferably less than 60cm -1 It is more preferable that it is less than 40 cm. -1 It is more preferable that F2 is 10 to 80 cm or less. -1 It is preferable that the distance is 15 to 60 cm. -1 More preferably, it is 25 to 40 cm. -1 It is even more preferable that: When F2 is equal to or greater than the lower limit, the stress generated when the CAM expands or contracts during charging and discharging can be alleviated, and the CAM is less likely to crack. As a result, the cycle retention rate is likely to improve. When F2 is equal to or less than the upper limit, the distribution of the distance of the Mn-O bond in the -MO-Mn- bond contained in the CAM is small, and the distance of the Mn-O bond in the -MO-Mn- bond is relatively uniform, so that the cycle retention rate is likely to improve.
[0037] In addition to the above requirements (1) and (2), the CAM preferably satisfies the following physical properties.
[0038] CAM's D 50 is preferably 2 μm or more, and more preferably 4 μm or more. 50 is preferably 30 μm or less, and more preferably 15 μm or less. 50 The thickness is preferably from 2 to 30 μm, and more preferably from 4 to 15 μm.
[0039] In powder X-ray diffraction measurement using CuKα radiation, the ratio of the peak intensity X2 to the peak intensity X1, X2 / X1, is preferably 0.005 or more, and more preferably 0.01 or more. X2 / X1 is preferably 0.06 or less, and more preferably 0.04 or less. X2 / X1 is preferably 0.005 to 0.06, and more preferably 0.01 to 0.04. When X2 / X1 is within the above range, the amount of heterogeneous phase in the CAM is in an appropriate range, and the structure becomes uniform, so that the cycle retention rate is easily improved.
[0040] The BET specific surface area of CAM is 0.2m 2 / g or more, and 0.3m 2 More preferably, it is 0.4m / g or more. 2 / g or more. The BET specific surface area is preferably 2m 2 / g or less, and 1.5m 2 / g or less is more preferable, and 1.25m 2 More preferably, the BET specific surface area is 0.2 to 2 m 2 / g, and 0.3 to 1.5m 2 / g is more preferable, and 0.4 to 1.25 m 2 When the BET specific surface area is within the above range, side reactions are less likely to occur at the reaction interface, and deterioration is suppressed, so that the cycle retention rate is likely to be improved.
[0041] <Composition> The M element is preferably at least one element selected from the group consisting of Mo and W, more preferably W. The CAM may further contain an M' element. Examples of the M' element include at least one element selected from the group consisting of Co, P, B, Ti, Zr, and Al. The amount (molar ratio) of the M' element to the total amount 1 of Ni and Mn in the CAM is preferably 0 to 0.5, more preferably 0.05 to 0.3, and even more preferably 0.1 to 0.2.
[0042] By containing the M element, the CAM forms a stable crystal structure in which lithium ions can be desorbed and inserted.
[0043] (Composition formula) The CAM is preferably represented by the following composition formula (I). Li 1+a Ni x Mn y M b M' c O2···(I) In the composition formula (I), 0 ≦ a ≦ 0.5, 0 < x < 1, 0 < y < 1, a + x + y + b + c = 1, 0 < b ≦ 0.1, and 0 ≦ c ≦ 0.3 are satisfied, M is the M element, and M' is the M' element.
[0044] a is preferably 0.02 or more, more preferably 0.05 or more. a is preferably 0.45 or less, more preferably 0.40 or less, and even more preferably 0.30 or less. The above upper and lower limit values of a can be arbitrarily combined. When a is equal to or greater than the lower limit value, the discharge capacity can be improved. When a is equal to or less than the upper limit value, the cycle retention rate can be improved. a is preferably 0 to 0.45, more preferably 0.02 to 0.40, and even more preferably 0.05 to 0.30.
[0045] x is preferably 0.01 or more, more preferably 0.05 or more, and even more preferably 0.10 or more. x is preferably 0.90 or less, more preferably 0.80 or less, even more preferably 0.70 or less, even more preferably 0.60 or less, and particularly preferably 0.45 or less. The upper and lower limits of x can be combined in any desired manner. When x is equal to or more than the lower limit, the discharge capacity can be improved, and when x is equal to or less than the upper limit, the cycle retention rate can be improved. x is preferably from 0.01 to 0.70, more preferably from 0.05 to 0.60, and further preferably from 0.10 to 0.45.
[0046] y is preferably 0.10 or more, more preferably 0.20 or more, and even more preferably 0.30 or more.y is preferably 0.80 or less, more preferably 0.70 or less, and even more preferably 0.60 or less. The above upper limit and lower limit values of y can be combined in any desired manner. When y is equal to or greater than the lower limit, the discharge capacity can be improved, and when y is equal to or less than the upper limit, the cycle retention rate can be improved. The value of y is preferably from 0.10 to 0.80, more preferably from 0.20 to 0.70, and further preferably from 0.30 to 0.60.
[0047] b is preferably 0.005 or more, more preferably 0.010 or more, and even more preferably 0.015 or more. b is preferably 0.10 or less, more preferably 0.05 or less, and even more preferably 0.03 or less. The above upper and lower limits of b can be combined in any desired manner. When b is equal to or more than the lower limit, the cycle retention rate can be improved, and when b is equal to or less than the upper limit, the discharge capacity can be improved. b is preferably from 0.005 to 0.10, more preferably from 0.010 to 0.05, and further preferably from 0.015 to 0.03.
[0048] From the perspective of improving the cycle retention rate, M is preferably at least one element selected from the group consisting of Mo and W, and more preferably W.
[0049] When the CAM contains the M' element, c is preferably 0.005 or more, and more preferably 0.01 or more. c is preferably 0.20 or less, more preferably 0.15 or less, and even more preferably 0.10 or less. The above upper and lower limit values of c can be arbitrarily combined. When c is equal to or greater than the lower limit value, the cycle retention rate can be improved. When c is equal to or less than the upper limit value, the discharge capacity can be improved. c is preferably from 0 to 0.20, more preferably from 0.005 to 0.20, even more preferably from 0.005 to 0.15, and particularly preferably from 0.01 to 0.10. Also, c may be 0.
[0050] When c is greater than 0, from the perspective of improving the cycle retention rate, M' is preferably at least one element selected from the group consisting of P, B, Co, and Al, and more preferably at least one element selected from the group consisting of Co and Al.
[0051] <Manufacturing method of CAM> The manufacturing method of CAM includes an MCC manufacturing step of manufacturing MCC, an M element-doped MCC manufacturing step of doping the obtained MCC with the M element to manufacture M element-doped MCC, a mixing step of mixing the obtained M element-doped MCC and a lithium compound, and a firing step of firing the obtained mixture.
[0052] (MCC manufacturing step) The MCC may be any of metal composite hydroxides, metal composite oxides, and mixtures thereof. The MCC manufacturing process involves reacting a solution of metal salts of Ni and Mn with a complexing agent and an alkaline solution. In this case, the resulting MCC is a metal composite hydroxide. The metal composite hydroxide can be manufactured by a known batch coprecipitation method or continuous coprecipitation method. The MCC contains Ni, Mn, and M1' in a molar ratio represented by the following formula (I'), for example. M1' is, for example, Co or Al. Ni:Mn:M1'=x':y':c' (I') In the formula (I'), x', y', and c' can be set so as to respectively satisfy x, y, and c in the composition formula (I).
[0053] Hereinafter, a method for producing MCC containing Ni and Mn will be described as an example. Specifically, a nickel salt solution, a manganese salt solution, and a complexing agent are reacted by the continuous coprecipitation method described in JP-A-2002-201028 to produce Ni. x’ Mn y’ It is possible to produce a metal complex hydroxide represented by (OH)2.
[0054] The nickel salt that is the solute of the nickel salt solution is not particularly limited, but for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0055] As the manganese salt which is the solute of the manganese salt solution, for example, at least one of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate can be used.
[0056] When producing MCC containing metal elements other than Ni and Mn (Co, Al, etc.), the sulfates, nitrates, chlorides, or acetates of the metal elements can be used as the solute.
[0057] The above metal salts are x’ Mn y’(OH)2. That is, the amount of each metal salt is specified so that the molar ratio of Ni and Mn in the mixed raw material solution containing the metal salts corresponds to x':y' in the above formula (I'). Water can be used as a solvent. When y' is within the range of the above formula (I'), X2 / X1 of CAM tends to be within the above range.
[0058] The complexing agent is capable of forming a complex with nickel ions and manganese ions in an aqueous solution, and examples thereof include ammonium ion donors such as ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride, hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine, with ammonium ion donors being preferred.
[0059] In the process for producing the metal composite hydroxide, a complexing agent may or may not be used. When a complexing agent is used, the amount of the complexing agent contained in the mixed solution containing the nickel salt solution, the manganese salt solution, and the complexing agent is preferably, for example, in a molar ratio greater than 0 and less than or equal to 2 relative to the total number of moles of the metal salts (nickel salt and manganese salt).
[0060] In the coprecipitation method, in order to adjust the pH value of the mixed solution containing the nickel salt solution, the manganese salt solution, and the complexing agent, an alkaline solution is added to the mixed solution before the pH of the mixed solution changes from alkaline to neutral. An example of the alkaline solution is an aqueous solution of an alkali metal hydroxide. An example of the alkali metal hydroxide is sodium hydroxide or potassium hydroxide.
[0061] In this specification, the pH value is a value measured when the temperature of the mixed liquid is 40° C. If the temperature of the mixed liquid sampled from the reaction tank is not 40° C., the mixed liquid is heated or cooled to 40° C. before measuring the pH.
[0062] When a complexing agent is continuously supplied to the reaction vessel in addition to the nickel salt solution and manganese salt solution, Ni and Mn react to produce Nix’ Mn y’ (OH)2 is produced.
[0063] The reaction temperature is preferably 20 to 80° C., more preferably 25 to 75° C., and further preferably 30 to 70° C. When the reaction temperature is within the above range, the crystallinity is increased, and the discharge capacity and cycle retention rate are increased.
[0064] The pH value in the reaction vessel is, for example, preferably 9 to 13, more preferably 9.5 to 12.5, and even more preferably 10 to 12. When the pH value is within the above range, the crystallinity is high and the discharge capacity is increased.
[0065] The reaction precipitate formed in the reaction tank is neutralized with stirring. The neutralization time of the reaction precipitate is, for example, 1 to 20 hours.
[0066] The reaction vessel used in the continuous coprecipitation method may be an overflow type reaction vessel for separating the reaction precipitate formed.
[0067] When producing a metal composite hydroxide by a batch coprecipitation method, examples of the reaction tank include a reaction tank not equipped with an overflow pipe, and an apparatus having a mechanism for concentrating the overflowed reaction precipitate in a concentration tank connected to an overflow pipe and circulating it back to the reaction tank.
[0068] Various gases may be supplied into the reaction vessel, for example, inert gases such as nitrogen, argon or carbon dioxide, oxidizing gases such as air or oxygen, or a mixture thereof.
[0069] After the above reaction, the neutralized reaction precipitate is washed with water and then isolated, for example, by dehydrating a slurry containing the reaction precipitate by centrifugation or suction filtration.
[0070] The isolated reaction precipitate is dried and sieved, if necessary, to obtain a metal composite hydroxide containing Ni and Mn.
[0071] The reaction precipitate is preferably washed with a washing liquid such as water, weak acid water, or an alkaline washing liquid, more preferably washed with an alkaline washing liquid, and even more preferably washed with an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution. It is preferable to wash with a washing solution having a mass of 10 times or more the mass of the reaction precipitate. In addition, the temperature of the washing solution used is preferably 30° C. or higher. Furthermore, if washing is performed in a batch system, it is preferable to perform washing two or more times. After washing with the weak acid water or alkaline washing solution, it is preferable to further wash with water to prevent compounds derived from the solution from remaining in the reaction precipitate.
[0072] The drying temperature is preferably 80 to 250° C., and more preferably 90 to 230° C. The drying time is preferably 0.5 to 24 hours, and more preferably 1 to 20 hours. The drying pressure may be normal pressure or reduced pressure.
[0073] When producing a metal composite oxide as MCC, a metal composite hydroxide may be heated to produce a metal composite oxide. If necessary, multiple heating steps may be performed. In this specification, the heating temperature refers to the set temperature of a heating device. In the case of multiple heating steps, the heating temperature refers to the temperature of the step in which the heating is performed at the highest temperature among the heating steps.
[0074] The heating temperature is preferably 400 to 700° C., and more preferably 450 to 680° C. When the heating temperature is within the above range, the metal composite hydroxide is sufficiently oxidized, and a metal composite oxide having a BET specific surface area in an appropriate range can be obtained.
[0075] The time for which the heating temperature is maintained may be 0.1 to 20 hours, and is preferably 0.5 to 10 hours. The rate of temperature rise to the heating temperature is, for example, 50 to 400° C. / hour. The heating atmosphere may be air, oxygen, nitrogen, argon, or a mixed gas thereof.
[0076] The inside of the heating device may be an atmosphere containing a suitable amount of oxygen. The oxygen-containing atmosphere may be a mixed gas atmosphere of an inert gas and an oxidizing gas, or may be an inert gas atmosphere in the presence of an oxidizing agent. By having the inside of the heating device be an atmosphere containing a suitable amount of oxygen, the transition metal contained in the metal composite hydroxide is oxidized to a suitable degree, making it easier to control the form of the metal composite oxide.
[0077] The oxygen or oxidizing agent in the oxygen-containing atmosphere should be sufficient to contain sufficient oxygen atoms to oxidize the transition metal.
[0078] When the oxygen-containing atmosphere is a mixed gas atmosphere of an inert gas and an oxidizing gas, the atmosphere in the heating device can be controlled by a method such as passing an oxidizing gas through the heating device or bubbling an oxidizing gas through the mixed liquid.
[0079] As the oxidizing agent, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorates, hypochlorites, nitric acid, halogens, ozone, or the like can be used.
[0080] Through the above steps, MCC can be produced.
[0081] (M element doped MCC manufacturing process) The manufacturing process for M element-doped MCC includes a spray mixing process in which a solution containing a compound containing an M element (hereinafter, sometimes referred to as "M solution") is sprayed onto the MCC while mixing the MCC, and a drying process in which the MCC sprayed with the M solution is dried.
[0082] [Spray mixing process] In the spray mixing step, the M solution is sprayed onto the MCC while the MCC is being mixed.
[0083] The compound containing the M element is not particularly limited as long as it is soluble in the solvent described below. For example, an oxide, ammonium salt, alkali metal salt, hydroxide, carbonate, nitrate, sulfate, halide, oxalate, alkoxide, or complex of the M element can be used. When the M element is W, examples of the compound include tungsten oxide, ammonium tungstate, tungsten alkoxide, sodium tungstate, and lithium tungstate, with lithium tungstate being preferred. When the M element is Nb, examples of the compound include niobium oxide, lithium niobate, niobium alkoxide, and niobium peroxo complex, with niobium peroxo complex being preferred. When the M element is Ta, examples of the compound include tantalum oxide and lithium tantalate, with lithium tantalate being preferred. When the M element is Mo, examples of the compound include molybdenum oxide and lithium molybdate, with lithium molybdate being preferred.
[0084] The solvent for dissolving the compound containing the element M is not particularly limited as long as it is a solvent capable of dissolving the compound, but is preferably an alkaline solution. Examples of the alkaline solution include aqueous solutions in which an alkaline compound such as ammonia or lithium hydroxide is dissolved, and an aqueous solution in which lithium hydroxide is dissolved is preferred.
[0085] The method for dissolving the compound containing the M element is not particularly limited, but for example, the compound containing the M element may be added to a reaction vessel equipped with a stirrer while stirring the solvent, and then dissolved. It is preferable that the compound containing the M element is completely dissolved in the solvent.
[0086] The content of the M element in the M solution is preferably 0.05 to 10 mol / L, more preferably 0.25 to 5 mol / L, and further preferably 0.5 to 2.0 mol / L. When lithium hydroxide is used as the solvent, the content of the alkali metal element relative to the total mass of the M solution is preferably 1 to 20 mol / L, more preferably 1.5 to 15 mol / L, and even more preferably 2.0 to 10 mol / L.
[0087] The M solution is sprayed onto the MCC while mixing the MCC. The temperature during spraying (such as the temperature of the MCC or the temperature of the solution) is preferably 0 to 50° C., more preferably 10 to 40° C., and even more preferably 15 to 30° C. When the temperature during spraying is within the above range, the M element is likely to be uniformly distributed in the MCC, and I2 / I1 is likely to fall within the above range.
[0088] The spray rate of the M solution is preferably 0.1 mL / min or more and less than 10 mL / min, more preferably 0.5 to 5 mL / min, and even more preferably 1.0 to 2.5 mL / min. When the spray rate is within the above range, the M element is likely to be uniformly distributed in the MCC, and I2 / I1 is likely to fall within the above range.
[0089] The discharge pressure when spraying the M solution is appropriately set depending on the specifications of the spraying device used, etc. As an example, it is preferable that MCC is sprayed and mixed at a discharge pressure of 0.05 MPa to 1 MPa for about 10 minutes to 600 minutes.
[0090] In this case, it is preferable to spray the M solution so that the molar ratio of the M element contained in the M solution to the total amount of metal elements contained in the MCC is 0.01 to 0.05. When the molar ratio of the M element is within the above range, F1, F2, and F2 / F1 of the CAM tend to be within the above ranges.
[0091] It is preferable to spray the M solution intermittently, for example by repeating a cycle of spraying for a certain period of time and then stopping the spraying.
[0092] In the case of producing a CAM containing one or more elements selected from the group consisting of P, B, Ti, and Zr as the M' element in the composition formula (I), a solution containing the M element and a compound containing the M' element may be sprayed in the spray mixing step.
[0093] [Drying process] In the drying step, the MCC sprayed with the M solution is dried to obtain M element-doped MCC.
[0094] The moisture content of the moisture derived from the M solution relative to the total mass of the MCC onto which the M solution is sprayed is preferably 5 to 30 mass%, more preferably 7.5 to 28 mass%, and even more preferably 10 to 26 mass%. When the moisture content is within the above range, the M element is easily distributed uniformly in the MCC, segregation of the M element that may occur during the drying step can be suppressed, and I2 / I1 tends to fall within the above range. The moisture content of the moisture derived from the M solution relative to the total mass of the MCC sprayed with the M solution is calculated by measuring the mass of the MCC before the spray mixing step and the mass of the MCC sprayed with the M solution, using the following formula. Moisture content of water derived from M solution (mass%) = 100 × moisture content in M solution × (mass of MCC sprayed with M solution - mass of MCC before spray mixing process) / mass of MCC sprayed with M solution (formula) The water content of the M solution refers to the mass ratio of water to the total amount of water, compound containing M element, and alkaline compound contained in the M solution used in the spray mixing step. The amounts of water, compound containing M element, and alkaline compound contained in the M solution correspond to the amounts charged when producing the M solution.
[0095] The spray mixing step is followed by the drying step. If the spray mixing step is performed at a high temperature (for example, 60°C or higher), the spray mixing step and the drying step can be performed simultaneously. However, according to the study by the inventors of the present application, it has been found that when the spray mixing step and the drying step are performed simultaneously, the M element is unlikely to be uniformly distributed in the MCC. That is, when the spray mixing step and the drying step are performed simultaneously, I2 / I1 is likely to be outside the above-mentioned range. On the other hand, it has been found that when the drying step is performed after the spray mixing step, the M element is likely to be uniformly distributed in the MCC. That is, when the drying step is performed after the spray mixing step, I2 / I1 is likely to be within the above-mentioned range.
[0096] The drying temperature is preferably 60 to 200° C., more preferably 80 to 180° C., and even more preferably 100 to 150° C. The drying pressure may be normal pressure or reduced pressure. In the case of reduced pressure, the drying pressure is preferably 0.01 to 10,000 Pa, more preferably 0.1 to 1000 Pa, and even more preferably 1 to 100 Pa. If the pressure is within the above range, the distribution of the M element is likely to be uniform.
[0097] The drying rate is preferably 0.005 to 10 mass% / min, more preferably 0.01 to 5 mass% / min, and even more preferably 0.02 to 1 mass% / min. The drying rate means the rate of decrease per unit time when the mass of the MCC onto which the M solution has been sprayed is taken as 100 mass%.
[0098] (Mixing process) The M element-doped MCC is mixed with a lithium compound. The lithium compound may be at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide hydrate, lithium oxide, lithium chloride, and lithium fluoride. Of these, lithium hydroxide and lithium carbonate or a mixture thereof are preferred.
[0099] The M element doped MCC and the lithium compound are mixed in consideration of the composition ratio of the final target product to obtain a mixture of the M element doped MCC and the lithium compound. The amount (molar ratio) of Li relative to the total amount of metal elements contained in the M element doped MCC is preferably 0.98 to 1.80, more preferably 1.10 to 1.70, and even more preferably 1.15 to 1.65. When lithium hydroxide is used as a solvent in the spray mixing step, the amount of Li includes the amount of Li derived from the lithium compound and the amount of Li derived from the lithium hydroxide sprayed onto the MCC. When the amount of Li is within the above range, the X2 / X1 of CAM is likely to be within the above range.
[0100] (Firing process) The resulting mixture is fired, which causes CAM crystals to grow.
[0101] The firing temperature in this specification refers to the temperature of the atmosphere in the firing apparatus, and means the maximum temperature that can be maintained (maximum maintained temperature). When the firing process has a plurality of firing stages, the firing temperature means the temperature of the stage in which firing is performed at the highest holding temperature among the firing stages.
[0102] The firing temperature is preferably 600 to 1200°C, more preferably 625 to 1100°C, further preferably 650 to 1050°C, and particularly preferably 650 to 1000°C. When the firing temperature is equal to or higher than the lower limit of the above range, the M element is easily dissolved in the CAM, and the CAM has a strong crystal structure. When the firing temperature is equal to or lower than the upper limit of the above range, the volatilization of lithium ions on the particle surface of the CAM can be reduced. When the firing temperature is within the above range, the F1, F2, F2 / F1, BET specific surface area, and D of the CAM can be reduced. 50 is likely to be within the above range.
[0103] The retention time in the firing is preferably 1 to 50 hours, more preferably 2 to 20 hours. When the retention time in the firing is equal to or less than the upper limit of the range, the volatilization of lithium ions is suppressed, and the deterioration of battery performance is suppressed. When the retention time in the firing is equal to or more than the lower limit of the range, the development of crystals is promoted, and the deterioration of battery performance is suppressed. When the retention time in the firing is within the range, the F1, F2, F2 / F1, and BET specific surface area of the CAM tend to be within the above-mentioned ranges.
[0104] In the firing step, the rate of temperature rise until the maximum holding temperature is reached is preferably 80° C. / hour or more, more preferably 100° C. / hour or more, and even more preferably 150° C. / hour or more. The rate of temperature rise until the maximum holding temperature is reached is calculated from the time from the start of temperature rise in the firing device until the holding temperature is reached.
[0105] The firing step preferably has a plurality of firing stages with different firing temperatures. For example, it is preferable to have a first firing stage and a second firing stage in which firing is performed at a higher temperature than the first firing stage. Furthermore, firing stages with different firing temperatures and firing times may be included.
[0106] As the firing atmosphere, air, oxygen, nitrogen, argon or a mixture of these gases may be used depending on the desired composition, and an oxygen-containing atmosphere is preferred.
[0107] The mixture of M element-doped MCC and lithium compound may be sintered in the presence of an inactive flux. The inactive flux may be added to such an extent that the initial capacity of the battery using CAM is not impaired, and may remain in the sintered product. As the inactive flux, for example, the inactive flux described in WO2019 / 177032A1 may be used.
[0108] The calcination apparatus used for calcination is not particularly limited, and may be, for example, a continuous static calcination furnace or a fluidized calcination furnace. Examples of the continuous static calcination furnace include a tunnel kiln or a roller hearth kiln. Examples of the fluidized calcination furnace include a rotary kiln.
[0109] As described above, CAM can be obtained by firing the mixture of MCC and the lithium compound.
[0110] <Lithium secondary battery> A positive electrode for a lithium secondary battery using the CAM of this embodiment will be described. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode. Furthermore, a lithium secondary battery suitable for use as a positive electrode will be described.
[0111] An example of a lithium secondary battery using the CAM of this embodiment has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0112] 1 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0113] First, as shown in the partially enlarged view of FIG. 1 , a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3, and then wound to form an electrode group 4.
[0114] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.
[0115] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.
[0116] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.
[0117] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0118] The shape of a lithium secondary battery having such an electrode group 4 can be any shape defined by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes can be used.
[0119] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.
[0120] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in
[0113] to
[0140] of WO2022 / 113904A1 can be used.
[0121] <All-solid-state lithium secondary battery> The CAM of this embodiment can be used as a CAM for an all-solid-state lithium secondary battery.
[0122] Fig. 2 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. The all-solid-state lithium secondary battery 1000 shown in Fig. 2 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a CAM and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400.
[0123] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.
[0124] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.
[0125] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. Additionally, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0126] The all-solid-state lithium secondary battery 1000 further has an insulator (not shown) that insulates the laminate 100 and the exterior body 200, and a sealing body (not shown) that seals the opening 200a of the exterior body 200.
[0127] As the exterior body 200, a container formed of a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used. Also, as the exterior body 200, a container formed by processing a laminate film with corrosion-resistant processing on at least one surface into a bag shape can be used.
[0128] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or sheet type), a cylindrical type, a rectangular type, or a laminate type (pouch type).
[0129] Although an example in which the all-solid-state lithium secondary battery 1000 has one laminate 100 is illustrated, the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell and a plurality of unit cells (laminates 100) are sealed inside the exterior body 200.
[0130] Regarding the all-solid-state lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in
[0151] to
[0181] of WO2022 / 113904A1 can be used.
Examples
[0131] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited thereto.
[0132] <Measurement of Various CAM Parameters> The various parameters of the CAM produced by the method described below were measured using the above-mentioned (Raman spectroscopic analysis parameters), (BET specific surface area), (composition), (50% cumulative volumetric grain size D 50 ), (Measurement of XRD pattern and X2 / X1), and (Confirmation of crystal structure) were performed using the measurement methods described above.
[0133] <Measurement of cycle maintenance rate> The cycle retention rate of the lithium secondary battery was measured by the method described above in (Cycle retention rate). A cycle retention rate of 96% or more was evaluated as being high.
[0134] [Example 1] Water was placed in a reaction vessel equipped with a rotary stirring device having stirring blades and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 30° C. (reaction temperature).
[0135] A mixed raw material solution 1 was prepared by mixing an aqueous nickel sulfate solution and an aqueous manganese sulfate solution so that the molar ratio of Ni:Mn was 50:50.
[0136] Under nitrogen flow, the mixed raw material liquid 1 and an aqueous solution of ammonium sulfate as a complexing agent were continuously added to a reaction vessel under stirring. The aqueous solution of sodium hydroxide was adjusted so that the pH of the mixed liquid in the reaction vessel became 11.7 (measurement temperature: 40°C), and a reaction precipitate 1 was obtained.
[0137] The reaction precipitate 1 was washed with water. After washing, it was dehydrated using a centrifuge, further washed with water, dehydrated, isolated, and dried at 105°C for 20 hours to obtain MCC1, a metal composite hydroxide containing Ni and Mn.
[0138] While mixing MCC1 at room temperature (25°C), W solution 1, which was prepared by dissolving lithium tungstate in a lithium hydroxide aqueous solution, was sprayed under the following spraying conditions. At this time, the amount (molar ratio) of W contained in W solution 1 relative to the total amount 1 of Ni and Mn contained in MCC1 was set to 0.03. The content of W in W solution 1 was 1.8 mol / L, and the content of Li relative to the total mass of W solution 1 was 7 mol / L. At the end of spraying, the moisture content of water derived from W solution 1 relative to the total mass of MCC1 onto which W solution 1 was sprayed was 15 mass%. Spray conditions Discharge pressure: 0.1MPa Spray rate: 1mL / min
[0139] The MCC1 onto which the W solution 1 was sprayed was dried in a reduced pressure (1.5 Pa) atmosphere at 120° C. at a drying rate of 0.025 mass % / min to evaporate water, thereby obtaining a W-doped MCC1.
[0140] Lithium hydroxide was weighed out so that the amount of Li (molar ratio) relative to the total amount 1 of Ni and Mn contained in W-doped MCC1 was 1.16. The amount of Li includes the amount of Li derived from the weighed lithium hydroxide and the amount of Li derived from the lithium hydroxide aqueous solution contained in the sprayed W solution 1. Mixture 1 was obtained by mixing W-doped MCC1 and lithium hydroxide.
[0141] The mixture 1 thus obtained was then fired in an oxygen atmosphere at 650°C for 5 hours, and then at 1000°C for 5 hours to obtain CAM1. Various parameters of CAM1 are shown in Table 1 (hereinafter, the same is true for Examples 2 and 3, and Comparative Examples 1 to 4). Note that a, x, y, b, and c in the composition in Table 1 are values corresponding to the composition formula (I).
[0142] A lithium secondary battery was produced using the obtained CAM1, and the cycle retention rate was measured. The results are shown in Table 1 (hereinafter, the same is shown for Examples 2 and 3 and Comparative Examples 1 to 4). Note that the "position of the maximum peak" in Table 1 refers to the position of the maximum peak in the range of 200 to 1000 cm in the Raman spectrum. -1 The position of the peak with the highest peak intensity within the range (unit: cmー1 For example, the maximum peak position of CAM1 is 597 cm ー1 and 200-1000 cm -1 In other words, the peak having the highest peak intensity in the range of I1 is P1. -1 The intensity of the peak obtained within the range is the highest.
[0143] [Example 2] While mixing the MCC1 at room temperature (25°C), W solution 2, which was prepared by dissolving lithium tungstate in an aqueous lithium hydroxide solution, was sprayed under the following spraying conditions. At this time, the amount (molar ratio) of W contained in W solution 2 relative to the total amount 1 of Ni and Mn contained in MCC1 was set to 0.01. The content of W in W solution 2 was 0.6 mol / L, and the content of Li relative to the total mass of W solution 2 was 2.5 mol / L. At the end of spraying, the moisture content of water derived from W solution 2 relative to the total mass of MCC1 onto which W solution 2 was sprayed was 15 mass%. Spray conditions Discharge pressure: 0.1MPa Spray rate: 1mL / min
[0144] The MCC1 onto which the W solution 2 was sprayed was dried in a reduced pressure (1.5 Pa) atmosphere at 120° C. at a drying rate of 0.025 mass % / min to evaporate the water, thereby obtaining a W-doped MCC2.
[0145] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount of Ni and Mn contained in W-doped MCC2 was 1.16, and W-doped MCC2 and lithium hydroxide were mixed to obtain CAM2 in the same manner as in Example 1. The amount of Li includes the amount of Li derived from the weighed lithium hydroxide and the amount of Li derived from the lithium hydroxide aqueous solution contained in the sprayed W solution 2.
[0146] [Example 3] Water was placed in a reaction vessel equipped with a rotary stirring device having stirring blades and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 30° C. (reaction temperature).
[0147] A mixed raw material solution 3 was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution so that the molar ratio of Ni:Co:Mn was 17:17:66.
[0148] Under nitrogen flow, the mixed raw material liquid 3 and an aqueous solution of ammonium sulfate as a complexing agent were continuously added to the reaction vessel under stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed liquid in the reaction vessel became 11.7 (measurement temperature: 40°C), and a reaction precipitate 3 was obtained.
[0149] The reaction precipitate 3 was washed with water. After washing, it was dehydrated in a centrifuge, further washed with water, dehydrated, isolated, and dried at 105° C. for 20 hours to obtain MCC3, which is a metal composite hydroxide containing Ni, Co, and Mn.
[0150] While mixing MCC3 at room temperature (25°C), W solution 3, which was prepared by dissolving lithium tungstate in a lithium hydroxide aqueous solution, was sprayed under the following spraying conditions. At this time, the amount (molar ratio) of W contained in W solution 3 relative to the total amount of Ni, Co, and Mn contained in MCC3, which was 1, was set to 0.01. The content of W in W solution 3 was 0.35 mol / L, and the content of Li relative to the total mass of W solution 3 was 1.3 mol / L. At the end of spraying, the moisture content of water derived from W solution 3 relative to the total mass of MCC3 onto which W solution 3 was sprayed was 25 mass%. Spray conditions Discharge pressure: 0.1MPa Spray rate: 1mL / min
[0151] The MCC3 onto which the W solution 3 had been sprayed was dried in a reduced pressure (1.5 Pa) atmosphere at 120° C. at a drying rate of 0.04 mass % / min to evaporate water, thereby obtaining a W-doped MCC3.
[0152] Lithium hydroxide was weighed out so that the amount of Li (molar ratio) relative to the total amount of Ni, Co, and Mn contained in W-doped MCC3 was 1.62. The amount of Li includes the amount of Li derived from the weighed lithium hydroxide and the amount of Li derived from the lithium hydroxide aqueous solution contained in the sprayed W solution 3. W-doped MCC3 and lithium hydroxide were mixed to obtain mixture 3.
[0153] The resulting mixture 3 was then calcined in an oxygen atmosphere at 900° C. for 10 hours to obtain CAM3.
[0154] [Comparative Example 1] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li contained in the lithium hydroxide relative to the total amount of Ni, Co, and Mn contained in the MCC3 was 1.5. Tungsten oxide powder was weighed out so that the amount (molar ratio) of W contained in the tungsten oxide powder relative to the total amount of Ni, Co, and Mn contained in the MCC3 was 1 was 0.01. Mixture 4 was obtained by mixing MCC3, lithium hydroxide, and tungsten oxide powder.
[0155] The resulting mixture 4 was then calcined in an oxygen atmosphere at 900° C. for 10 hours to obtain CAM4.
[0156] [Comparative Example 2] While mixing the MCC1 at room temperature (25°C), W solution 5, which was prepared by dissolving lithium tungstate in an aqueous lithium hydroxide solution, was sprayed under the following spraying conditions. At this time, the amount (molar ratio) of W contained in W solution 5 relative to the total amount of Ni and Mn contained in MCC1 (1) was set to 0.03. The content of W in W solution 5 was 1.8 mol / L, and the content of Li relative to the total mass of W solution 5 was 7.3 mol / L. At the end of spraying, the moisture content of water derived from W solution 5 relative to the total mass of MCC1 onto which W solution 5 was sprayed was 15 mass%. Spray conditions Discharge pressure: 0.1MPa Spray rate: 10mL / min
[0157] The MCC1 onto which the W solution 5 was sprayed was dried in a reduced pressure (1.5 Pa) atmosphere at 120° C. at a drying rate of 0.025 mass % / min to evaporate water, thereby obtaining a W-doped MCC5.
[0158] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount of Ni and Mn contained in W-doped MCC5 was 1.11, and W-doped MCC5 and lithium hydroxide were mixed to obtain CAM5 in the same manner as in Example 1. The amount of Li includes the amount of Li derived from the weighed lithium hydroxide and the amount of Li derived from the aqueous lithium hydroxide solution contained in the sprayed W solution 5.
[0159] [Comparative Example 3] While mixing the MCC1 at 80°C, W solution 6, which was prepared by dissolving lithium tungstate in an aqueous lithium hydroxide solution, was sprayed under the following spraying conditions to obtain W-doped MCC6. At this time, the amount (molar ratio) of W contained in W solution 6 relative to the total amount of Ni and Mn contained in MCC1 (1) was set to 0.03. The content of W in W solution 6 was 1.8 mol / L, and the content of Li relative to the total mass of W solution 6 was 7.4 mol / L. At the end of spraying, the moisture content of water derived from W solution 6 relative to the total mass of W-doped MCC6 was 1 mass%. Spray conditions Discharge pressure: 0.1MPa Spray rate: 0.3mL / min
[0160] Lithium hydroxide was weighed out so that the amount of Li (molar ratio) relative to the total amount of Ni and Mn contained in W-doped MCC 6 was 1.11. The amount of Li includes the amount of Li derived from the weighed lithium hydroxide and the amount of Li derived from the lithium hydroxide aqueous solution contained in the sprayed W solution 6. W-doped MCC 6 and lithium hydroxide were mixed to obtain mixture 6.
[0161] CAM6 was obtained in the same manner as in Example 1, except that the obtained mixture 6 was used.
[0162] [Comparative Example 4] While mixing the MCC1 at 80° C., the W solution 6 was sprayed under the following spraying conditions to obtain W-doped MCC 7. At this time, the amount (molar ratio) of W contained in the W solution 6 relative to the total amount of Ni and Mn contained in MCC1 (1) was set to 0.03. At the end of spraying, the moisture content of the water derived from the W solution 6 relative to the total mass of the W-doped MCC 7 was 2 mass%. Spray conditions Discharge pressure: 0.6MPa Spray rate: 10mL / min
[0163] Lithium hydroxide was weighed out so that the amount of Li (molar ratio) relative to the total amount of Ni and Mn contained in W-doped MCC7, which was 1, was 1.11. The amount of Li includes the amount of Li derived from the weighed lithium hydroxide and the amount of Li derived from the lithium hydroxide aqueous solution contained in the sprayed W solution 6. Mixture 7 was obtained by mixing W-doped MCC7 and lithium hydroxide.
[0164] CAM7 was obtained in the same manner as in Example 1, except that the obtained mixture 7 was used.
[0165] [Table 1]
[0166] CAMs 1 to 7 have a layered structure, and their main crystal structures were assigned to the space group R-3m. It was found that the lithium secondary batteries manufactured using the CAMs of Examples 1 to 3, which satisfy the requirements (1) and (2), had higher cycle retention rates than the lithium secondary batteries manufactured using the CAMs of Comparative Examples 1 to 4, which do not satisfy the requirement (2). [Explanation of symbols]
[0167] Reference Signs List 1...separator, 2...positive electrode, 2a...positive electrode active material layer, 2b...positive electrode current collector, 3...negative electrode, 4...electrode group, 5...battery can, 6...electrolyte, 7...top insulator, 8...sealing body, 10...lithium secondary battery, 21...positive electrode lead, 31...negative electrode lead, 100...laminated body, 110...positive electrode, 111...positive electrode active material layer, 112...positive electrode current collector, 113...external terminal, 120...negative electrode, 121...negative electrode active material layer, 122...negative electrode current collector, 123...external terminal, 130...solid electrolyte layer, 200...exterior body, 200a...opening, 1000...all-solid-state lithium secondary battery
Claims
1. A positive electrode active material for a lithium secondary battery comprising Li, Mn, Ni, and an M element, the M element being at least one element selected from the group consisting of Nb, Ta, Mo, and W, and satisfying the following requirements (1) and (2): (1) It has a layered structure. (2) In Raman spectroscopy with an excitation wavelength of 532 nm, -1 The peak is P1, 630-670 cm -1 The peak intensity of P1 is I 1 , and the peak intensity of P2 is I 2 When I 2 / I 1 is 0.20 or more and 0.68 or less.
2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein F2 / F1 is 0.55 or more and 1.35 or less, where F1 is the half width of P1 and F2 is the half width of P2.
3. 3. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, which is represented by the following composition formula (I): Li 1+a Ni x Mn y M b M' c O 2 ・・・(I) [In the composition formula (I), 0≦a≦0.5, 0<x<1, 0<y<1, a+x+y+b+c=1, 0<b≦0.1, and 0≦c≦0.3 are satisfied, and M′ is at least one element selected from the group consisting of P, B, Co, Ti, Zr, and Al.]
4. BET specific surface area is 0.2m 2 / g or more 2m 2 The positive electrode active material for a lithium secondary battery according to claim 1 or 2, wherein the Mo content is 1 / g or less.
5. In powder X-ray diffraction measurement using CuKα radiation, the peak intensity X of the peak present in the range of 2θ = 18.7 ± 1 ° is 1 The peak intensity X of the peak existing in the range of 2θ=20.7±1° 2 The ratio of X 2 / X 1 The positive electrode active material for a lithium secondary battery according to claim 1 or 2, wherein is 0.005 or more and 0.06 or less.
6. I 1 is 200 cm -1 More than 1000cm -1 3. The positive electrode active material for a lithium secondary battery according to claim 1, which has the highest peak intensity obtained within the following ranges:
7. A positive electrode for a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery according to claim 1 or 2.
8. A lithium secondary battery comprising the positive electrode according to claim 7.
Citation Information
Patent Citations
Positive electrode active material for non-aqueous electrolyte secondary battery and method for manufacturing same, and non-aqueous electrolyte secondary battery using said positive electrode active material
WO2016171081A1